KUALITAS PELAYANAN EXTRA BED DI BATIQA HOTEL PEKANBARU - Fitri, Resi Anda; Sidiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine the extrabed service procedures and to find out the quality of extra bed service in the batiqa hotels Pekanbaru which consists of four elements of service namely speed, accuracy, friendliness, skill. Extra Bed is an extra bed placed in the guest room. This study uses descriptive quantitative research methods. And the population of this study is all guests who order extra beds in Batiqa Pekanbaru Hotels. According to Masri Singarimbun (1987: 152) the researcher himself is the one who determines the sample considering energy, cost, time so the sample can be taken at a minimum. then the author decided to take 50 users and those who have used extra beds at Batiqa Pekanbaru Hotels. Data collection techniques in this study used observation, questionnaires, and documentation. The data analysis technique used is descriptive quantitative analysis, where data that has been obtained through questionnaires and observations in the field, all information collected, studied so that it becomes a unified whole .. Based on the research that has been done, the results of processing data show guest responses to the extra bed service at Batiqa Hotel Pekanbaru is good. Keywords: Service Quality, Extra Bed